Mitochondrial gene expression in elite cyclists: effects of high-intensity interval exercise - Psilander, N.; Wang, L.; Westergren, J.; Tonkonogi, M.; Sahlin, K. (European Journal of Applied Physiology, 2010)
Little is known about the effect of training on genetic markers for mitochondrial biogenesis in elite athletes. We tested the hypothesis that low-volume sprint interval exercise (SIE) would be as effective as high-volume interval exercise (IE). Ten male cyclists competing on national elite level (W max 403 ± 13 W, VO2peak 68 ± 1 mL kg-1 min-1) performed two interval exercise protocols: 7 × 30-s "all-out" bouts (SIE) and 3 × 20-min bouts at ~87% of VO2peak (IE). During IE, the work was eightfold larger (1,095 ± 43 vs. 135 ± 5 kJ) and the exercise duration 17 times longer (60 vs. 3.5 min) than during SIE. Muscle samples were taken before and 3 h after exercise. The mRNA of upstream markers of mitochondrial biogenesis [peroxisome proliferator-activated receptor- coactivator-1 (PGC-1a), PGC-1a-related coactivator (PRC) and peroxisome proliferator-activated receptor d (PPARd)] increased to the same extent after SIE and IE (6-, 1.5- and 1.5-fold increase, respectively). Of the downstream targets of PGC-1a, mitochondrial transcription factor A (Tfam) increased only after SIE and was significantly different from that after IE (P < 0.05), whereas others increased to the same extent (pyruvate dehydrogenase kinase, PDK4) or was unchanged (nuclear respiratory factor 2, NRF2). We conclude that upstream genetic markers of mitochondrial biogenesis increase in a similar way in elite athletes after one exercise session of SIE and IE. However, since the volume and duration of work was considerably lower during SIE and since Tfam, the downstream target of PGC-1a, increased only after SIE, we conclude that SIE might be a time-efficient training strategy for highly trained individuals.